1998
DOI: 10.1074/jbc.273.4.2199
|View full text |Cite
|
Sign up to set email alerts
|

Triose-phosphate Isomerase (TIM) of the Psychrophilic BacteriumVibrio marinus

Abstract: The purification and characterization of triose-phosphate isomerase from the psychrophilic bacterium Vibrio marinus (vTIM) is described. Crystal structures of the vTIM-sulfate complex and the vTIM-2-phosphoglycolate complex (at a 2.7-Å resolution) are also presented. The optimal growth temperature of Vibrio marinus is 15°C. Stability studies show that vTIM is an unstable protein with a half-life of only 10 min at 25°C. The vTIM sequence is most closely related to the sequence of Escherichia coli TIM (eTIM) (66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
0
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(116 citation statements)
references
References 38 publications
5
108
0
3
Order By: Relevance
“…The only non-Gly residue that shows a positive 9 is Lys12 (49.5/52.5 and 54.7/50.9 in the A/B subunits of the 3PG and G3P complexes, respectively). Indeed, this residue has a positive 9 in the unbound PfTIM and also in enzymes from other sources (Noble et al, 1991;Alvarez et al, 1998;Zhang et al, 1994). The ligands were well de®ned in both the crystallographically independent subunits, although the ligands are better de®ned in one of the subunits than in the other.…”
Section: Figurementioning
confidence: 99%
“…The only non-Gly residue that shows a positive 9 is Lys12 (49.5/52.5 and 54.7/50.9 in the A/B subunits of the 3PG and G3P complexes, respectively). Indeed, this residue has a positive 9 in the unbound PfTIM and also in enzymes from other sources (Noble et al, 1991;Alvarez et al, 1998;Zhang et al, 1994). The ligands were well de®ned in both the crystallographically independent subunits, although the ligands are better de®ned in one of the subunits than in the other.…”
Section: Figurementioning
confidence: 99%
“…In addition to mutational studies, the involvement of these factors in protein adaptation is suggested from comparative studies between psychrophilic enzymes and their heat-stable homologues based on homology models and 3D structures. An increased number of crystallographic structures of psychrophilic enzymes from bacteria and cold-adapted fishes have been previously elucidated (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) (29) and fish trypsin (37). Other structures should become available soon, as crystals of three other cold-active enzymes have been obtained (43)(44)(45).…”
Section: Psychrophilic Enzymesmentioning
confidence: 99%
“…Although some features of the cold-adapted enzymes have been proposed on the basis of comparisons between the primary structures of the corresponding enzymes from various organisms with different ranges of growth temperature, it is difficult to distinguish exactly whether they are attributable to cold adaptation or to phylogenetic differences between the organisms (Sheridan et al, 2000). On the other hand, analyses of the crystal structures of cold-adapted enzymes has revealed the diversity of their mechanisms for cold adaptation (Fields & Somero, 1998;Russell et al, 1998;Kim et al, 1999;Alvarez et al, 1998;Bentahir et al, 2000).…”
Section: Introductionmentioning
confidence: 99%